Combination of fibrates with obeticholic acid is able to normalise biochemical liver tests in patients with difficult‐to‐treat primary biliary cholangitis. Issue 10 (25th March 2021) - Soret, Pierre‐Antoine; Lam, Laurent; Carrat, Fabrice; Smets, Lena; Berg, Thomas; Carbone, Marco; Invernizzi, Pietro; Leroy, Vincent; Trivedi, Palak; Cazzagon, Nora; Weiler‐Normann, Christina; Alric, Laurent; et al.
Summary: Background: Obeticholic acid (OCA) and fibrates are second‐line therapies for patients with primary biliary cholangitis (PBC) with an inadequate response to ursodeoxycholic acid (UDCA). Aim: To know whether OCA and fibrates, administered together in combination with UDCA, have additive beneficial effects in patients with difficult‐to‐treat PBC. Methods: PBC patients treated for ≥3 months with UDCA, OCA and fibrates (bezafibrate or fenofibrate) due to failure of either second‐line therapy were included in a multicentre, uncontrolled retrospective cohort study. Changes in biochemical liver tests and pruritus were analysed using a generalised linear mixed‐effect model. Results: Among 58 patients included, half received OCA as second‐line and fibrates as third‐line therapy (Group OCA‐Fibrate), while the other half had the inverse therapeutic sequence (Group Fibrate‐OCA). The mean duration of triple therapy was 11 months (range 3‐26). Compared to dual therapy, triple therapy was associated with a significant gain in alkaline phosphatase (ALP) reduction: 22% per first year (95% CI 12%‐31%), an effect that was stronger in OCA‐Fibrate than in Fibrate‐OCA group. Triple therapy was associated with a 3.4 (95% CI 1.4‐8.2) odds ratio (OR) of reaching normal ALP and with a significant decrease in gamma‐glutamyl transpeptidase (GGT), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and total bilirubin. The ORs of achieving the Paris‐2 and Toronto criteria of adequate biochemical response were 6.8 (95% CI 2.8‐16.7) and 9.2 (95% CI 3.4‐25.1) respectively. Finally, triple therapy significantly improved pruritus in OCA‐Fibrate but not in Fibrate‐OCA group. Conclusions: Triple therapy with UDCA, OCA and fibrates is able to normalise biochemical liver tests and improve pruritus in patients with difficult‐to‐treat PBC. Abstract : Triple therapy with UDCA, OCA, and Fibrate was associated with a 3.4 (95%CI 1.4‐8.2) odds ratio of achieving normal levels of alkaline phosphatase (ALP).